ANALISIS BIOEKOLOGI PERAIRAN PESISIR UNTUK PENGEMBANGAN BUDIDAYA KEPITING BAKAU (Scylla serrata, Forskal) DENGAN HUTAN MANGROVE (SylvoCrab) - Rustam Rustam; Jayadi Jayadi; Darmawati Darmawati (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2023)
The aims of this research are; (1) Ecological analysis of coastal waters for development of cultivating mangrove crab (2) Assessing the condition of mangrove forest ecosystems, (3) testing prototypes of technology for crab cultivation businesses in mangrove forest areas. Primary data includes physical and chemical parameters as well as mangrove forest conditions. The results of observations of the condition of the mangrove area, for the Important Index Value (INP) of mangroves, Rhizopora, sp sampling I (191.2), sampling II (181.7), sampling III (205.0), this shows that in sampling III for The Rhizopora sp type has a greater role in maintaining the sustainability of the ecosystem. For the dominance index value, the value for all stations is 0.02 – 0.03. This shows that there is no species that dominates other species or the community is in a stable condition. Meanwhile, the species diversity index value in the entire sampling area has low species diversity, namely 0 < H < 2. The results of physical observations of waters, the results of tidal data processing using the Admiralty method show that the mean sea level (MSL) is 200.41 cm, The lowest low sea level (LLWL) is 112.86 cm and the highest high sea level (HHWL) is 279.41 cm, the tidal range (range) is 166.36 cm. From the value of the Formzahl number (F value = 1.89) it can be concluded that the type of tide around the observation location is a mixed tidal type that tends to be single daily. The results of observations of water salinity parameters at the research location ranged from 25.0 - 27.1 ‰ with an average value of average 26.0 5 ‰, pH, nitrite (NO2), nitrate (NO3) and phosphate (PO4) in water. The average pH value of 6.90, the average nitrite content value of 0.020, the average nitrate content value of 0.236 and the average phosphate content of 0.145 indicate good water quality for mariculture purposes, and also indicate the condition of the waters that have not been polluted.The growth of mud crabs fed with crab food had a good growth effect compared to those given trash fish feed.